MENINGKATKAN HASIL BELAJAR MATEMATIKA MATERI PERKALIAN MELALUI MEDIA GAME PERSIK - Reski Nurasmi; Haerul Syam; Ma'rup (Jurnal Pendidikan Sang Surya, 2024)
ABSTRACT: Improving Mathematics Learning Outcomes on Multiplication Materials through Media Game Persik (Asik Multiplication) Class II Students UPT SPF Inpres Andi Tonro. The main problem in this study is that students lack confidence in solving math problems, students tend to be passive in the learning process, pay less attention to the teacher's explanation and math learning outcomes are still low. This study aims to improve math learning outcomes of multiplication material through peach game media for class II B UPT SPF Inpres Andi Tonro students. This type of research uses Classroom Action Research (PTK). The research subjects were class II B UPT SPF Inpres Andi Tonro students totaling 22 students. This research consists of two cycles, each cycle includes four stages, namely planning, implementation, observation, and reflection. The instruments in this study include observation sheets, and learning outcomes tests. The analysis technique used was descriptive statistical analysis. The results of the study using peach game media in learning math multiplication material can increase the activity and learning outcomes of class II B UPT SPF Inpres Andi Tonro students as evidenced by an increase in student learning activities student learning activeness in cycle I of 48.86% increased in cycle II by 75.54% while the expected target was reached 55%. The increase in student learning outcomes in cycle I obtained an average value of student learning outcomes of 60.91, then in cycle II obtained an average value of student learning outcomes of 84.54. Students' mathematics learning completeness also increased, in cycle I there were 9 students or 40.91%, while in cycle II there were 18 students or 81.81% classical completeness was achieved classically because the number of students who completed more than 80%. Based on the research results, it can be concluded that the mathematics learning outcomes of class II B UPT SPF Inpres Andi Tonro students through the application of peach game media have increased.